Comprehensive Analysis of Derivational and Inflectional Morphemes for English Language Acquisition - Zaniar, Savira; Authar, Nailul; Aquariza, Novi Rahmania; Rihlah, Jauharotur; Sucita, Adelia Ayu Putri (Jurnal Pendidikan Indonesia, 2024)
Morphology plays a crucial role in students' language acquisition. This study delves into the distinctions between inflectional and derivational morphemes, aiming to enhance comprehension of these concepts. By investigating word creation processes and observed alterations, the study illustrates the profound impact of prefixes and suffixes on words, shedding light on their significance in language learning. Students frequently require clarification when distinguishing between inflectional and derivational morphemes during learning. To enhance comprehension of this subject, this present study initially investigated the definitions and subcategories of these two terms outlined in various literary sources. Next, it provided a concise overview of the critical distinctions between inflectional and derivational morphemes. These analyses aim to determine the word created by derivational morphemes, the word formed by inflectional morphemes, the process by which the specified word is formed, and the types of observed alterations. The author implements the descriptive qualitative approach. It will discover that each morpheme possesses its function and influences the base word's meaning, word class, or grammatical function. This study illustrates the impact of prefixes and suffixes on words.